Hydrological Operation Requirements for Restoration and Improving Water Quality of Abu Zirig Marsh - Ammar Adel Ali; Haitham A. Hussein; Mahmoud S. Al Khafaji (Engineering and Technology Journal, 2010)
A hydrological routing study for Abu Zirig Marsh was carried out toestimate the hydrological state within the marsh for the Present and future conditions of the marsh.The water surface elevation, area and storage within the marsh at the present and for the future conditions were estimated and the effect of uncontrolling outlets on the hydrological and water quality state of the marsh at the present conditions was specified. The salt mass balance equation was used to estimate the inflow and outflow discharges that required for reducing the effect of evapotranspiration on the water quality and flashing out the accumulated mass of salts and then improving the marsh water quality. This equation was applied on the future conditions of themarsh and inflow and outflow discharges that required for this purposes were estimated. The results of the hydrological routing for the present conditions showed that the maximum water surface area is 79 km2 which occur during Spring. While it is between 34 to 43 km2 during Summer and Autumn and it can not be increased during these months since the outlet of the marsh is uncontrolled. The TDS concentration within the marsh increases during the months of high evapotranspiration although the inflow increases during these months. For the future conditions, the inflow discharges required to sustain the restoration requirements must be increased to decrease the deterioration in the marsh water quality. These discharges increase with the increase in the marsh areaduring the months of high evapotranspiration values.